2019
DOI: 10.1136/bmjgast-2019-000294
|View full text |Cite
|
Sign up to set email alerts
|

Screening for coeliac disease in children and adults living in a slum of Dhaka, Bangladesh

Abstract: Background and objectiveSerological screening with a confirmation through biopsy has improved the understanding of coeliac disease (CD) epidemiology worldwide. Prevalence of CD in Bangladesh is not yet explored and therefore, we aimed to assess the seroprevalence of CD in slum-dwelling malnourished children and adults in Dhaka.MethodsSerum samples were collected from three different cohorts: stunted (length-for-age Z-scores (LAZ) <−2) and at risk of stunting children (LAZ <−1 to −2) and malnourished adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“…The commonest etiology responsible for duodenitis in studies conducted in Western countries was found to be celiac disease (CD), which accounted for 32% of the total cases 28 . No children in the present study were found positive for celiac disease on serology 29 and the IEL count was also insignificant, which is an important histopathologic marker of CD 30 . As the unique feature for all the children was only being stunted or at risk of stunting and they also did not have any pathology diagnosed by endoscopy, the high prevalence of duodenitis among these children was possibly related to EED and not due to celiac disease or any other GI disease 16 .…”
Section: Discussioncontrasting
confidence: 56%
“…The commonest etiology responsible for duodenitis in studies conducted in Western countries was found to be celiac disease (CD), which accounted for 32% of the total cases 28 . No children in the present study were found positive for celiac disease on serology 29 and the IEL count was also insignificant, which is an important histopathologic marker of CD 30 . As the unique feature for all the children was only being stunted or at risk of stunting and they also did not have any pathology diagnosed by endoscopy, the high prevalence of duodenitis among these children was possibly related to EED and not due to celiac disease or any other GI disease 16 .…”
Section: Discussioncontrasting
confidence: 56%
“…Celiac disease is the best-known cause of villous atrophy. However, celiac was found to be uncommon among the people in the same region in our earlier analysis 38 . Participants in the current study were slum dwellers and lived in a poor socioeconomic environment where EED and bacterial overgrowth in intestine is common [39][40][41] .…”
Section: Comparison Of Histologic Findings Between Lewis Posiɵve and ...mentioning
confidence: 58%
“…The commonest etiology responsible for duodenitis in studies conducted in Western countries was found to be celiac disease (CD), which accounted for 32% of the total cases [ 27 ]. No children in the present study were found positive for celiac disease on serology [ 28 ] and the IEL count was also insignificant, which is an important histopathologic marker of CD [ 29 ]. As the unique feature for all the children was only being stunted or at risk of stunting and they also did not have any pathology diagnosed by endoscopy, the high prevalence of duodenitis among these children was possibly related to EED and not due to celiac disease or any other GI disease [ 16 ].…”
Section: Discussionmentioning
confidence: 99%